TANGGUNG JAWAB HUKUM DALAM PERJANJIAN PEMINJAMAN - Himmatul Aliyah (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Loan agreement is a legal contract involving a lender and a borrower. This paper discusses the legal responsibilities arising within the context of a loan agreement. In this agreement, the lender has an obligation to provide funds or items to be borrowed, while the borrower is responsible for repaying the loan in accordance with the agreed-upon terms. The legal responsibilities of the lender encompass aspects such as providing honest and transparent information regarding loan terms, as well as safeguarding the security and integrity of the borrowed assets. On the other hand, the borrower is expected to comply with applicable regulations and repay the loan in accordance with the agreement, including the payment of any agreed-upon interest. This article also explores the legal implications when breaches occur in a loan agreement, whether by the lender or the borrower. The analysis involves concepts of accountability, legal sanctions, and dispute resolution efforts. Understanding the legal responsibilities in a loan agreement is crucial for all parties involved to carry out the agreement with integrity and compliance with the applicable laws.